The Influence Of Brand Ambassador And Consumer Habits Of Purchasing Decisions For Nature Republic Products (Survey On Nature Republic’s Consumers In Tasikmalaya) - Reza Ayu Fauziah; Budhi Wahyu Fitriadi; Depy Muhamad Pauzy (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the influence of brand ambassador and consumer habits of purchasing decisions for Nature Republic products.. The method used in this research is a quantitative approach method with a survey method. The population in this study is unknown and the sample is taken using random sampling. While the determination of the number of respondents (samples) using purposive sampling as many as 100 respondents. The analytical tool used is multiple regression analysis. SPSS version 25 is used. The results show that brand ambassador and consumer habits simultaneously have a significant effect on purchasing decisions for nature republic products. Brand ambassador partially has a significant effect on purchasing decisions. Consumer habits have a significant effect on purchasing decisisons.